The Role of Diverse Immune Cells in Sarcoidosis - Zhang, Hui; Costabel, Ulrich; Dai, Huaping (Frontiers in Immunology, 2021)
Sarcoidosis is a systemic inflammatory disorder of unknown etiology characterized by tissue infiltration with macrophages and lymphocytes and associated non-caseating granuloma formation. The disease primarily affects the lungs. Patients suffering from sarcoidosis show a wide range of clinical symptoms, natural history and disease outcomes. Originally described as a Th1-driven disease, sarcoidosis involves a complex interplay among diverse immune cells. This review highlights recent advances in the pathogenesis of sarcoidosis, with emphasis on the role of different immune cells. Accumulative evidence suggests Th17 cells, IFN-γ-producing Th17 cells or Th17.1 cells, and regulatory T (Treg) cells play a critical role. However, their specific actions, whether protective or pathogenic, remain to be clarified. Macrophages are also involved in granuloma formation, and M2 polarization may be predictive of fibrosis. Previously neglected cells including B cells, dendritic cells (DCs), natural killer (NK) cells and natural killer T (NKT) cells were studied more recently for their contribution to sarcoid granuloma formation. Despite these advances, the pathogenesis remains incompletely understood, indicating an urgent need for further research to reveal the distinct immunological events in this process, with hope to open up new therapeutic avenues and if possible, to develop preventive measures.